DEVELOPMENT OF TEACHING MATERIALS BASED ON GUIDED INQUIRY LEARNING MODEL TO IMPROVE STUDENT'S MATHEMATIC COMMUNICATION ABILITY - Winanda Marito; Nova Riani (Sean Institute, 2022)
The product of this research is a teaching material that meets the valid and effective criteria in the form of Student Worksheets (LKS), and Mathematical Communication Ability tests which are designed based on the Guided Inquiry learning model to improve students' mathematical communication skills. The development model used is a 4-D model consisting of four stages, namely defining, designing, developing and distributing. This research was conducted in SMP Karya Bhakti Medan. The population of this study were all students of SMP Karya Bhakti Medan which consisted of 156 people spread over 7 parallel classes.